2019
DOI: 10.1016/j.celrep.2019.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Subregions Express Distinct Dendritic Transcriptomes that Reveal Differences in Mitochondrial Function in CA2

Abstract: SUMMARY RNA localization is one mechanism that neurons use to spatially and temporally regulate gene expression at synapses. Here, we tested the hypothesis that cells exhibiting distinct forms of synaptic plasticity will have differences in dendritically localized RNAs. Indeed, we discovered that each major subregion of the adult mouse hippocampus expresses a unique complement of dendritic RNAs. Specifically, we uncovered over 1,000 differentially expressed dendritic RNAs, suggesting that RNA localization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 104 publications
8
91
2
Order By: Relevance
“…Mouse RNA-sequencing and human microarray data RNA-Seq data were obtained from previously published work [66,67] (Gene Expression Omnibus Super-Series GSE116343). Briefly, laser capture microdissected samples (n = 3 per region) targeting the cell body region of CA1, CA2, CA3, and dentate gyrus were obtained and sequenced using an Illumina NextSeq 500 instrument, acquiring 100 bp paired-ends reads to a depth of 50 million reads per sample ( + /-10 mil).…”
Section: Single-molecule Fluorescent In Situ Hybridization and Image mentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse RNA-sequencing and human microarray data RNA-Seq data were obtained from previously published work [66,67] (Gene Expression Omnibus Super-Series GSE116343). Briefly, laser capture microdissected samples (n = 3 per region) targeting the cell body region of CA1, CA2, CA3, and dentate gyrus were obtained and sequenced using an Illumina NextSeq 500 instrument, acquiring 100 bp paired-ends reads to a depth of 50 million reads per sample ( + /-10 mil).…”
Section: Single-molecule Fluorescent In Situ Hybridization and Image mentioning
confidence: 99%
“…Briefly, laser capture microdissected samples (n = 3 per region) targeting the cell body region of CA1, CA2, CA3, and dentate gyrus were obtained and sequenced using an Illumina NextSeq 500 instrument, acquiring 100 bp paired-ends reads to a depth of 50 million reads per sample ( + /-10 mil). Raw reads were pseudoaligned to GENCODE (vM12) gene models and the mm10 mouse genome and quantitated per gene using Salmon (v0.9.1, indexed with kmer size 31) [66][67][68]. The ratio of MR:GR was calculated from the normalized counts for each sample and averaged for each hippocampal subregion.…”
Section: Single-molecule Fluorescent In Situ Hybridization and Image mentioning
confidence: 99%
“…Thus, distinct molecular pathways might convey the generation of neurons in these two structures. Moreover, several studies have shown that there is subregion specific transcriptional differences along the longitudinal axis [5,6,36]. Importantly, most of these studies exploit RNA sequencing approaches to investigate protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been unclear how widespread this effect is and whether it was driven primarily by tandem UTRs or ALEs. To address this, we used LABRAT to analyze the relative APA status of 26 paired transcriptomic datasets from cell body and projection samples from neuronal cells, NIH 3T3 cells, and MDA-MB231 cells (Farris et al, 2019;Goering et al, 2019;Hudish et al, 2020;Mardakheh et al, 2015;Minis et al, 2013;Taliaferro et al, 2016;Tushev et al, 2018;Wang et al, 2017;Zappulo et al, 2017).…”
Section: Alternative Polyadenylation Isoforms Are Differentially Locamentioning
confidence: 99%